Application of the Levenberg-Marquardt Algorithm in Solving the Economic Emission Dispatch Problem Integrating Renewable Energy - Dridi, T.; Jouini, H.; Mami, A.; El Mhamedi, A.; Dafaoui, E. M. (Engineering, Technology & Applied Science Research, 2022)
The Economic Emission Dispatch (EED) is a multi-objective optimization problem that seeks to find the optimal balance between the reduction of the generation costs and the pollutant emissions of power thermal plants while respecting power balance and several operational restrictions. This balance could be carried out by proper scheduling power generation of the committed units to fulfill the power demands considering emissions. This paper presents a novel application of the conventional Levenberg-Marquardt Algorithm (LMA) optimization approach to solve the EED problem with the integration of renewable energy. Wind and solar energy were chosen to be injected into the system’s power balance constraint. The combined EED objective function with Valve Point Effects (VPE) consideration was modeled using price penalty and weight factors. This study showed the effectiveness of the chosen optimization technique and the influence of injecting renewable energy along with traditional power resources on reducing total cost and pollutant emissions. The proposed method was applied to the IEEE 9-bus test system and tested in Matlab.